Non-bleeding antimicrobial hydrophilic fibers, dressings and methods of making and using the same

CN122960015APending Publication Date: 2026-10-23WINNER MEDICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611292224.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

该方法旨在解决现有技术中存在的问题,包括但不限于:1、银抗菌纤维敷料,银离子会释放造成生物安全性问题;2、对于类似吸附胍盐类亲水纤维敷料,双胍类物质通过物理吸附在亲水性纤维上,使用时极易释放,有一定的降低抗菌效果和生物安全性隐患问题;3、化学接枝胍盐类水凝胶和亲水纤维敷料,胍类化合物接枝过程采用有机溶剂,且含羧基基团较多,对未化学接枝完的胍类化合物有极强的吸附作用,仅仅依靠有机溶剂洗涤很难去除,难以达到真正无胍类抗菌化合物释放目的

Benefits of technology

(1)本发明所述制备方法通过控制第一次醚化产物的取代度,获得遇水不发生凝胶化的低取代羧甲基纤维素钠纤维,突破了高取代纤维素吸水成胶、无法在水相中进行接枝反应的技术限制,可完全采用纯水相缓冲体系开展酰胺化反应,无需使用有机溶剂参与反应过程。该工艺既避免了有机溶剂带来的环境污染与回收成本,也能让缩合剂、活化剂与胍类化合物在水相中分散更均匀,提升反应接枝效率,同时温和的水相条件对纤维素纤维骨架损伤更小,保障纤维的力学性能与结构完整性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122960015A_ABST
    Figure CN122960015A_ABST
Patent Text Reader

Abstract

The application provides a non-overflowing antibacterial hydrophilic fiber, a dressing and a preparation method and application thereof, and relates to the technical field of medical dressings. The preparation method of the non-overflowing antibacterial hydrophilic fiber comprises the following steps: performing a first etherification reaction on fiber raw materials to obtain low-substituted degree sodium carboxymethyl cellulose; performing an amidation reaction on the low-substituted degree sodium carboxymethyl cellulose and a guanidine compound, and then performing washing with a high-salt aqueous solution to obtain low-substituted sodium carboxymethyl cellulose fiber grafted with a guanidine salt; and performing a second etherification reaction on the low-substituted sodium carboxymethyl cellulose fiber grafted with the guanidine salt to obtain high-substituted sodium carboxymethyl cellulose fiber grafted with the guanidine salt. The fiber and the dressing prepared by the method have the guanidine antibacterial agent firmly grafted by a covalent bond, realize zero overflow of the antibacterial component, have long-acting antibacterial and high-water-absorbing and liquid-locking performances, and the water-phase reaction process is green and controllable, and the product has excellent biological safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical dressing technology, and in particular to a non-overflowing antibacterial hydrophilic fiber, a dressing, its preparation method, and its application. Background Technology

[0002] Sodium carboxymethyl cellulose (CMC-Na) is an important water-soluble cellulose ether derivative obtained by carboxylation modification of cellulose, with the molecular formula [C6H7O2(OH)4(OCH2COONa)3]. The CMC-Na molecular chain is rich in carboxyl groups (-COO). - Sodium carboxymethyl cellulose (CMC) contains hydrophilic functional groups such as hydroxyl (-OH), which have high water absorption properties and can absorb large amounts of water to form a gel on its surface. This property of CMC is particularly advantageous in the manufacture of wound dressings with absorbent and gel-forming properties.

[0003] Currently, bactericides used to kill or eliminate harmful microorganisms mainly include natural antibacterial agents (chitosan and its derivatives, etc.), inorganic antibacterial agents (silver-based antibacterial agents, etc.), and organic antibacterial agents (quaternary ammonium salts, guanidine salts, phenolic ethers, pyrroles, etc.). Silver is a useful antibacterial agent with broad-spectrum activity and compatibility with mammalian tissues. Silver salt solutions can kill bacteria by disrupting their cell walls and denaturing their enzymes. There have been many suggestions to incorporate silver into wound dressings to give them the advantages of silver's antibacterial properties, such as adding silver to sodium calcium alginate or sodium carboxymethyl cellulose to prepare antibacterial dressings.

[0004] CN101187153A discloses a simple method for rapidly adding silver ions to calcium alginate fibers. The method involves immersing the calcium alginate fibers in a mixture of a silver ion-containing compound and sodium carboxymethyl cellulose powder, allowing the silver-containing substance to be physically adsorbed onto the fiber surface. However, the physical adsorption force is weak, and the silver-containing substance is easily detached during subsequent fiber processing and use, resulting in low silver content, poor antibacterial durability, and uncontrollable silver ion release.

[0005] CN1935268A discloses a nano-silver calcium alginate antibacterial dressing, which is prepared by spraying nano-silver paste onto calcium alginate fiber products or directly immersing fibers in nano-silver paste, followed by dehydration and drying. This method is simple, but the nano-silver particles have weak bonding with the fibers and are easily washed away by wound exudate.

[0006] US7,385,101 discloses an antibacterial textile material suitable for wound dressings, which mixes textile fibers with a metallic silver coating on the surface with alginate fibers and produces a wound dressing with a silver content of up to 8% by a nonwoven method. However, the release rate of silver ions from metallic silver is low, limiting its antibacterial effect; and the silver-plated fibers have poor moisture absorption, which is not conducive to wound healing.

[0007] CN114575140A discloses a method for preparing sodium carboxymethyl cellulose (CCMC) silver fibers. The method involves treating CCMC sodium fibers with citric acid to remove sodium, followed by electrolysis to react carboxylate ions with silver ions to generate CCMC sodium silver fibers. This method grafts silver ions onto the fiber molecules via chemical bonds, avoiding the harmful effects of free silver. However, the process involves electrolysis equipment and a proton exchange membrane, resulting in high costs, and the silver ion release rate is difficult to control.

[0008] CN109898323A discloses a method for preparing medical antibacterial fibers, which involves mixing alginate fibers or sodium carboxymethyl cellulose fibers containing carboxylate ions with soluble silver salts, and generating submicron or micron-sized silver particles or silver-containing compound particles on the fiber surface through reduction or precipitation reactions. However, in these methods of loading silver onto hydrophilic fibers, the silver is released after liquid absorption, which raises concerns about biosafety.

[0009] CN102462860A discloses a fibrous wound dressing with antibacterial properties and its preparation method. The dressing is a fabric made of fibers coated with a polyhexamethylene biguanide solution, or a fabric coated with a polyhexamethylene biguanide solution. This dressing can be used continuously for 7 days. However, the polyhexamethylene biguanide component is only adsorbed onto the fabric. The carboxyl groups on the gelled fibers chemically adsorb the biguanide component, leading to easy leaching of the biguanide component from the wound exudate. This leaching reduces the dressing's antibacterial properties and poses a certain biosafety risk due to the biguanide component being absorbed by the human body.

[0010] CN103920180A discloses a chitosan hydrogel for antibacterial dressings and its preparation method. The method involves introducing carboxyl groups onto chitosan via free radical polymerization, then using a condensing agent and an activator to amidate the introduced carboxyl groups with the antibacterial agent polyhexamethylene guanidine hydrochloride, thereby grafting the antibacterial agent polyhexamethylene guanidine hydrochloride onto the chitosan. Finally, the modified chitosan aqueous solution is reacted with a crosslinking agent to obtain the chitosan hydrogel for antibacterial dressings. However, this invention does not disclose the grafting rate of guanidine, and the washing process only uses ethanol. The amino and carboxyl groups of polyhexamethylene guanidine hydrochloride have extremely strong ion adsorption effects, and ethanol alone cannot completely wash away the unreacted polyhexamethylene guanidine hydrochloride. This is because polyhexamethylene guanidine hydrochloride is a cationic polymer hydrochloride, with extremely low solubility (<1%) in ethanol, making it almost insoluble. Carboxylated chitosan is an anionic polyelectrolyte that binds to polyhexamethylene guanidine hydrochloride through strong electrostatic attraction. Ethanol has weak polarity and cannot effectively break this bond.

[0011] CN107137749A discloses an antibacterial wound dressing, its preparation method, and its application. The antibacterial wound dressing is obtained by amidation reaction of sodium carboxymethyl cellulose and guanidine compounds. This method utilizes the amidation reaction to graft guanidine salt antibacterial agents onto sodium carboxymethyl cellulose fibers via amide bonds. However, the utilization rate of biguanide is only 0.21-8.7%, and the utilization rate of guanidine compounds is extremely low. Furthermore, the grafting rate of guanidine is greatly affected by the degree of substitution; the higher the degree of substitution (the higher the proportion of carboxyl groups in the fiber, and the more groups participating in the amidation reaction), the higher the grafting rate of biguanide. Fibers with a substitution level below 0.2% exhibit both low grafting rates of biguanide compounds and low liquid absorption and retention. Similarly, this invention cannot completely wash away unamidated grafted biguanide compounds using only a mixture of ethanol and water. Moreover, for sodium carboxymethyl cellulose with the same substitution, a higher grafting rate of biguanide results in a relative decrease in water absorption. This is because sodium carboxymethyl cellulose undergoes self-crosslinking during the amidation reaction, reducing liquid absorption.

[0012] It is evident that the amidation reaction and washing processes in the two inventions mentioned above require the participation of organic solvents, which is not only costly but also makes it difficult to completely wash away guanidine compounds, and organic solvents easily pollute the environment. The reason why similar inventions use organic solvent reaction systems is that the hydrophilic fibers absorb water to form a gel, thus making it impossible to use pure water solvents or low-concentration organic solvents for the reaction and subsequent washing processes. Furthermore, the amidation reaction in the two inventions requires pH control, but neither invention improves pH control, which may lead to a decrease in PHMB grafting efficiency.

[0013] In view of this, the present invention is hereby proposed. Summary of the Invention

[0014] The purpose of this invention is to provide a non-overflowing antibacterial hydrophilic fiber, a dressing, its preparation method, and its application. This invention controls the degree to which the hydroxyl groups on the raw material fiber are replaced by carboxymethyl groups, preventing gel formation upon contact with water. Then, an amidation reaction is carried out with a guanidine salt antibacterial agent in a pH buffer system of pure water. Simultaneously, the antibacterial fiber after the grafting reaction is completed is thoroughly washed with a high-salt aqueous solution to completely remove unreacted guanidine salt substances and reaction activators. Finally, a secondary etherification reaction is used to increase the degree of substitution of the antibacterial fiber, achieving a high water absorption effect, thus giving the dressing both high antibacterial properties and high water absorption. This method aims to address existing problems, including but not limited to: 1. Silver antibacterial fiber dressings, where the release of silver ions poses biosafety concerns; 2. For similar adsorbed guanidine salt hydrophilic fiber dressings, biguanides are physically adsorbed onto hydrophilic fibers, but are easily released during use, potentially reducing antibacterial efficacy and raising biosafety risks; 3. Chemically grafted guanidine salt hydrogels and hydrophilic fiber dressings, where the grafting process uses organic solvents containing numerous carboxyl groups, exhibiting a strong adsorption effect on incompletely grafted guanidine compounds, making removal difficult using only organic solvent washing, thus failing to achieve truly guanidine-free antibacterial compound release. Furthermore, the need for large amounts of organic solvent washing significantly increases production costs.

[0015] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for preparing non-overflow antibacterial hydrophilic fibers, the method comprising: The fiber raw material undergoes a first etherification reaction to obtain sodium carboxymethyl cellulose with a low degree of substitution; After the sodium carboxymethyl cellulose with low degree of substitution and guanidine compounds undergo an amidation reaction, it is washed with a high-salt aqueous solution to obtain sodium carboxymethyl cellulose fiber with grafted guanidine salts. The grafted guanidine salt low-substituted sodium carboxymethyl cellulose fiber undergoes a second etherification reaction to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the low-substituted sodium carboxymethyl cellulose is less than 0.25; the degree of substitution of the grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber is greater than 0.35.

[0016] Furthermore, the first etherification reaction includes the following steps: The fiber raw material is first treated with an alkaline solution, then with a sodium chloroacetate solution, and finally neutralized, washed, and dried to obtain the sodium carboxymethyl cellulose with low degree of substitution.

[0017] Furthermore, the fiber raw material includes any one or a combination of at least two of Tencel fiber, cotton fiber, bamboo fiber, and viscose fiber, preferably Tencel fiber.

[0018] Further, the alkali content in the alkali solution is 2-8% by mass; the mass ratio of the fiber raw material to the alkali solution is 1:(10-20); the temperature of the alkali solution treatment is 25-40℃; the treatment time is 20-40 min; and the alkali is sodium hydroxide.

[0019] Further, the sodium chloroacetate solution contains 5-20% sodium chloroacetate by mass; the mass ratio of the fiber raw material to sodium chloroacetate is 1:(0.2-0.4); the sodium chloroacetate solution is treated at a temperature of 60-80°C; and the sodium chloroacetate solution is treated for 1-3 hours.

[0020] Furthermore, the neutralization employs an acidic pH adjuster; the acidic pH adjuster includes any one or a combination of at least two of lactic acid, citric acid, acetic acid, and hydrochloric acid, preferably lactic acid.

[0021] Furthermore, the pH of the neutralized fiber is 5-7.

[0022] Furthermore, the washing process uses pure water.

[0023] Furthermore, the amidation reaction includes the following steps: A condensing agent, activator, guanidine compound, buffer solution, and sodium carboxymethyl cellulose with low substitution degree are mixed and subjected to an amidation reaction.

[0024] Furthermore, the condensing agent includes carbodiimide compounds, preferably any one or a combination of at least two of EDC, DCC, and DIC.

[0025] Furthermore, the activator includes NHS and / or HOBt.

[0026] Furthermore, the guanidine compounds include any one or a combination of at least two of polyhexamethylene guanidine and its derivatives, and polyhexamethylene biguanide and its derivatives.

[0027] Further, the mass ratio of the condensing agent, activator, guanidine compound and sodium carboxymethyl cellulose with low degree of substitution is 1:(0.02~0.12):(0.01~0.08):(0.01~0.2).

[0028] Further, the buffer solution includes any one or a combination of at least two of MES buffer, HEPES buffer, and PBS buffer; the pH of the buffer solution is 5.0 to 6.0, and the concentration of the buffer solution is 0.02 to 0.1 mol / L; the mass ratio of the low-substituted sodium carboxymethyl cellulose to the buffer solution is 1:(15 to 25).

[0029] Furthermore, the amidation reaction is carried out at a temperature of 20-30°C for 1-3 hours.

[0030] Furthermore, the concentration of the high-salt aqueous solution is 0.5~2 mol / L.

[0031] Furthermore, the solute salt in the high-salt aqueous solution includes sodium chloride and / or sodium sulfate.

[0032] Furthermore, the washing temperature of the high-salt aqueous solution is 50~60℃, and the washing time of the high-salt aqueous solution is 30~90 min.

[0033] Furthermore, the second etherification reaction includes the following steps: A mixed solution is obtained by mixing alkali, sodium chloroacetate, pH buffer, ethanol, and water. The grafted guanidine salt low-substituted sodium carboxymethyl cellulose fiber is placed in the mixed solution for treatment, followed by neutralization, washing, and drying to obtain the grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber.

[0034] Further, the mixed solution comprises, by mass percentage: 0.5-1.5% alkali, 1-3% sodium chloroacetate, 0.1-0.5% pH buffer, with the remainder being an aqueous ethanol solution; the alkali is sodium hydroxide; the pH buffer includes any one or a combination of at least two of sodium lactate, sodium citrate, sodium acetate, sodium hydrogen phosphate, and sodium dihydrogen phosphate; the volume ratio of ethanol to water in the aqueous ethanol solution is (75-85):(25-15).

[0035] Furthermore, the mass ratio of the grafted guanidine salt low-substituted carboxymethyl cellulose sodium fiber to the mixed solution is 1:(15~25).

[0036] Furthermore, the processing temperature is 60~80℃, and the processing time is 0.5~1.5 h.

[0037] Furthermore, the neutralization employs an acidic pH adjuster; the acidic pH adjuster includes any one or a combination of at least two of lactic acid, citric acid, acetic acid, sodium lactate, and sodium dihydrogen phosphate, preferably lactic acid and sodium lactate.

[0038] Furthermore, the pH of the neutralized fiber is 5-7.

[0039] Furthermore, the washing process uses an aqueous ethanol solution; the volume ratio of ethanol to water in the aqueous ethanol solution is (70~80):(30~20).

[0040] In a second aspect, the present invention provides a non-overflow antibacterial hydrophilic fiber, wherein the non-overflow antibacterial hydrophilic fiber is prepared by the preparation method of the non-overflow antibacterial hydrophilic fiber as described in the first aspect.

[0041] Thirdly, the present invention provides a non-overflow antibacterial hydrophilic fiber dressing, the non-overflow antibacterial hydrophilic fiber dressing comprising grafted guanidine salt-based highly substituted sodium carboxymethyl cellulose fiber prepared by the preparation method of the non-overflow antibacterial hydrophilic fiber described in the first aspect, or the non-overflow antibacterial hydrophilic fiber described in the second aspect.

[0042] Fourthly, the present invention provides a method for preparing a non-overflowing antibacterial hydrophilic fiber dressing as described in the third aspect, the method comprising: The grafted guanidine salt highly substituted carboxymethyl cellulose sodium fiber or the non-overflow antibacterial hydrophilic fiber is needle-punched to form a nonwoven fabric, thereby obtaining the non-overflow antibacterial hydrophilic fiber dressing.

[0043] Furthermore, the weight is controlled at 100~400g / m³. 2 The pre-puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the main puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the main puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the net walking speed is 0.5~2 m / min.

[0044] Fifthly, the present invention provides the use of a non-overflowing antimicrobial hydrophilic fiber dressing according to the second aspect or the third aspect in the preparation of a wound dressing having absorbent and / or gel-forming properties.

[0045] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the present invention obtains low-substituted sodium carboxymethyl cellulose fibers that do not gel upon contact with water by controlling the degree of substitution of the first etherification product. This overcomes the technical limitations of high-substituted cellulose fibers, which absorb water and gel, and cannot undergo grafting reactions in an aqueous phase. The amidation reaction can be carried out entirely using a pure aqueous buffer system without the need for organic solvents. This process avoids environmental pollution and recycling costs associated with organic solvents, and allows condensing agents, activators, and guanidine compounds to disperse more evenly in the aqueous phase, improving the grafting efficiency. At the same time, the mild aqueous phase conditions cause less damage to the cellulose fiber skeleton, ensuring the mechanical properties and structural integrity of the fibers.

[0046] (2) The preparation method of the present invention adopts a stepwise etherification process design. First, low-substitution fibers are prepared to complete guanidine grafting, and then the substitution degree of the final product is improved through a second etherification. This solves the technical contradiction in the existing one-step process where high substitution degree is conducive to water absorption but grafting is difficult, and low substitution degree is easy to graft but has insufficient water absorption performance. This process can independently control the guanidine grafting process and the fiber water absorption performance construction process, which not only ensures the feasibility and grafting effect of amidation grafting, but also precisely controls the final substitution degree of the fiber through secondary etherification, giving the dressing excellent liquid absorption and liquid retention capacity, and achieving simultaneous improvement of antibacterial performance and water absorption and moisturizing performance.

[0047] (3) The preparation method described in this invention uses an amidation reaction to firmly graft guanidine antibacterial components onto the cellulose fiber skeleton in a covalent form. The antibacterial components are stably bound to the fiber matrix, and no precipitation or loss occurs during the absorption of wound exudate by the dressing. It can maintain a stable antibacterial effect for a long time, avoiding the defects of rapid detachment and short antibacterial time of antibacterial components in physically adsorbed dressings. At the same time, the characteristic of no antibacterial component leakage eliminates the safety hazards caused by the absorption of free guanidine substances by the wound, reduces the irritation of the dressing to the wound, and is suitable for the long-term care needs of various acute and chronic wounds. It has excellent biocompatibility and safety of use.

[0048] (4) The preparation method of this invention targets the strong electrostatic adsorption between the anionic groups of sodium carboxymethyl cellulose and cationic guanidines. It uses a high-salt aqueous solution to wash the amidated product, thereby disrupting the electrostatic adsorption through high ionic strength. This thoroughly washes away unreacted free guanidine compounds, as well as residual condensing agents, activators, and reaction byproducts, solving the technical problem that traditional ethanol washing cannot completely remove electrostatic adsorption residues. This washing step is set before the secondary etherification, utilizing the non-gelling characteristic of low-substituted fibers to ensure thorough washing and avoid the problem of difficult purification of highly absorbent fibers. The final product has low impurity residue, uniform and stable performance, and excellent batch consistency. Attached Figure Description

[0049] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0050] Figure 1 The diagram shows the state of sodium carboxymethyl cellulose with different degrees of substitution in water.

[0051] Figure 2 The infrared spectrum of CMC, the raw material used in Example 1, and the antibacterial wound dressing prepared therefrom. Detailed Implementation

[0052] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0053] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0054] In a first aspect, the present invention provides a method for preparing non-overflow antibacterial hydrophilic fibers, the method comprising: The fiber raw material undergoes a first etherification reaction to obtain sodium carboxymethyl cellulose with a low degree of substitution; After the sodium carboxymethyl cellulose with low degree of substitution and guanidine compounds undergo an amidation reaction, it is washed with a high-salt aqueous solution to obtain sodium carboxymethyl cellulose fiber with grafted guanidine salts. The grafted guanidine salt low-substituted sodium carboxymethyl cellulose fiber undergoes a second etherification reaction to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the low-substituted sodium carboxymethyl cellulose is less than 0.25; the degree of substitution of the grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber is greater than 0.35.

[0055] It should be noted that this invention controls the degree to which the hydroxyl groups on cellulose fibers are replaced by carboxymethyl groups, preventing them from forming gels when exposed to water. Then, it undergoes an amidation reaction with guanidine salt antibacterial agents in an aqueous solution. Simultaneously, the modified Tencel fibers after the grafting reaction are thoroughly washed with a high-salt aqueous solution to remove unreacted guanidine salts and reaction activators. Finally, the low-substituted carboxymethyl cellulose sodium fibers grafted with guanidine salts undergo a secondary etherification reaction to increase the degree of substitution of the antibacterial fibers, achieving a high water absorption effect. This invention simultaneously achieves the beneficial effects of stable antibacterial properties with zero precipitation, a green and efficient process, and a synergistic improvement in water absorption and antibacterial performance. The reasons are as follows: First, by controlling the low degree of carboxymethyl substitution in the fiber, it does not gel upon contact with water, overcoming the limitation of traditional high-substituted cellulose that cannot be grafted in an aqueous phase. The amidation reaction can be completed in a pure aqueous buffer system without the need for organic solvents, making it green, cost-effective, and ensuring a more uniform and complete grafting reaction. Second, by utilizing a high-salt aqueous solution to disrupt the strong electrostatic adsorption between anionic cellulose and cationic guanidines, and by conducting washing in a low-substituted, non-gel state, free guanidines and reaction impurities can be thoroughly removed, achieving zero spillage of antibacterial components and improving biosafety. Third, the post-treatment secondary etherification increases the final degree of substitution, resolving the contradiction between grafting effect and water absorption performance in the one-step method, simultaneously achieving long-lasting antibacterial effect and high liquid absorption and retention capacity. Fourth, through the amidation reaction, the guanidine antibacterial components are firmly grafted to the cellulose fiber skeleton in the form of covalent bonds. The antibacterial components are stably bound to the fiber matrix, and no precipitation or loss occurs during the absorption of wound exudate by the dressing, thus maintaining a stable antibacterial effect for a long time.

[0056] At the same time, it needs to be emphasized that, such as Figure 1 As shown, the states of sodium carboxymethyl cellulose fibers with different degrees of substitution in water are clearly visible. At a substitution degree of 0.2, the sodium carboxymethyl cellulose fibers still exhibit a fibrous state; at 0.3, the fibers have partially gelled, and no obvious fibrous strands are visible; at 0.4, the fibers are completely gelled, appearing as a transparent gel. Therefore, when the substitution degree is 0.3 or higher, the fibers have gelled, making grafting with guanidine compounds impossible.

[0057] As an optional implementation, the degree of substitution of the low-substituted sodium carboxymethyl cellulose is 0.25 or less, for example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, etc.

[0058] In a preferred embodiment, the degree of substitution of the low-substituted sodium carboxymethyl cellulose is 0.15 to 0.25, for example, it can be 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, etc.

[0059] It should be noted that the optimal degree of substitution of sodium carboxymethyl cellulose (SMC) with low substitution is 0.15–0.25. This range represents the best balance between the feasibility of aqueous-phase amidation and the grafting effect, ensuring both reaction stability and product performance uniformity. When the degree of substitution is below 0.15, the number of carboxymethyl functional groups on the cellulose backbone may be insufficient, failing to provide enough amidation reaction sites and making it difficult to achieve the guanidine grafting amount required for effective antibacterial activity. Furthermore, the uniformity of fiber reactivity is poor. However, when the degree of substitution is above 0.25, the degree of swelling of the fiber upon contact with water increases significantly. Although it does not completely gel, it hinders the diffusion of the reaction reagents into the interior, reducing grafting uniformity and weakening the elution efficiency of high-salt washing.

[0060] As an optional implementation, the first etherification reaction includes the following steps: The fiber raw material is first treated with an alkaline solution, then with a sodium chloroacetate solution, and finally neutralized, washed, and dried to obtain the sodium carboxymethyl cellulose with low degree of substitution.

[0061] It should be noted that this stepwise first etherification process is suitable for the low-substitution degree modification requirements of fibrous raw materials, offering strong reaction controllability and excellent product uniformity. The initial alkali treatment gently swells the cellulose fiber backbone, activating hydroxyl groups to generate sodium cellulose, providing uniform reactive sites for subsequent etherification and avoiding problems such as excessive local substitution or uneven reaction. Then, sodium chloroacetate is added for directional etherification, facilitating precise control of the carboxymethyl grafting amount and stably obtaining the target low-substitution degree product. Finally, neutralization, washing, and drying terminate the reaction, thoroughly removing residual alkali and by-salt impurities to avoid interference with the subsequent amidation system, while completely preserving the fiber morphology.

[0062] As an optional implementation, the fiber raw material includes any one or a combination of at least two of Tencel fiber, cotton fiber, bamboo fiber, and viscose fiber.

[0063] In a preferred embodiment, the fiber raw material is Tencel fiber.

[0064] It should be noted that Tencel (lyocell fiber) is a regenerated cellulose fiber with a regular structure, uniform hydroxyl distribution, and consistent and stable etherification reactivity. This allows for precise control of the low substitution degree range, and the fiber morphology can be well maintained after modification. It is also less prone to gelation when exposed to water, meeting the requirements of aqueous amidation reactions and high-salt washing processes. Furthermore, Tencel exhibits excellent dry and wet strength, maintaining good mechanical properties even after multiple chemical modifications and needle punching processes. It also possesses excellent biocompatibility, low impurity content, and high medical safety, ensuring stable quality and performance of dressings.

[0065] As an optional implementation, during the first etherification reaction, the mass percentage of alkali in the alkaline solution is 2-8%, for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc.

[0066] As an optional implementation, during the first etherification reaction, the mass ratio of the fiber raw material to the alkali solution is 1:(10~20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, etc.

[0067] As an optional implementation, during the first etherification reaction, the temperature of the alkaline treatment is 25~40℃, for example, it can be 25℃, 26℃, 27℃, 28℃, 29℃, 30℃, 31℃, 32℃, 33℃, 34℃, 35℃, 36℃, 37℃, 38℃, 39℃, 40℃, etc.

[0068] As an optional implementation, during the first etherification reaction, the alkaline treatment time is 20-40 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.

[0069] As an optional implementation, the base used in the first etherification reaction is sodium hydroxide.

[0070] As an optional implementation, during the first etherification reaction, the sodium chloroacetate solution contains 5-20% sodium chloroacetate by mass, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.

[0071] As an optional implementation, during the first etherification reaction, the mass ratio of the fiber raw material to sodium chloroacetate is 1:(0.2~0.4), for example, it can be 1:0.2, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.3, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.4, etc.

[0072] As an optional implementation, during the first etherification reaction, the sodium chloroacetate solution is treated at a temperature of 60-80°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc.

[0073] As an optional implementation, during the first etherification reaction, the treatment time of the sodium chloroacetate solution is 1 to 3 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, etc.

[0074] As an optional implementation, during the first etherification reaction, the neutralization is performed using an acidic pH adjuster.

[0075] As an optional implementation, during the first etherification reaction, the acidic pH adjuster includes any one or a combination of at least two of lactic acid, citric acid, acetic acid, and hydrochloric acid.

[0076] In a preferred embodiment, the acidic pH adjuster is lactic acid during the first etherification reaction.

[0077] As an optional implementation, during the first etherification reaction, the pH of the neutralized fiber is 5 to 7, for example, it can be 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, etc.

[0078] As an optional implementation, the washing process during the first etherification reaction is carried out using pure water.

[0079] As an optional implementation, the amidation reaction includes the following steps: A condensing agent, activator, guanidine compound, buffer solution, and sodium carboxymethyl cellulose with low substitution degree are mixed and subjected to an amidation reaction.

[0080] It should be noted that reacting the condensing agent, activator, guanidine compound, and low-substituted fiber in the same buffer system allows for continuous carboxyl activation and amide bonding processes, effectively reducing hydrolytic loss of active intermediates and improving reaction efficiency and guanidine grafting rate. Simultaneously, the buffer solution maintains a stable reaction pH, the low-substituted fiber exhibits excellent dispersibility in the aqueous phase, reagents can fully contact all reaction sites on the fiber, resulting in high grafting uniformity, and the mild reaction conditions also preserve the fiber skeletal structure intact.

[0081] As an optional implementation, the condensing agent includes carbodiimide compounds.

[0082] As an optional implementation, the condensing agent includes any one or a combination of at least two of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), N,N'-dicyclohexylcarbodiimide (DCC), and N,N'-diisopropylcarbodiimide (DIC).

[0083] As an optional implementation, the activator includes N-hydroxysuccinimide (NHS) and / or 1-hydroxybenzotriazole (HOBt).

[0084] As an optional implementation, the guanidine compound includes any one or a combination of at least two of polyhexamethylene guanidine and its derivatives, and polyhexamethylene biguanide and its derivatives.

[0085] As an optional implementation, the mass ratio of the condensing agent, activator, guanidine compound, and sodium carboxymethyl cellulose with low substitution degree is 1:(0.02~0.12):(0.01~0.08):(0.01~0.2); Among them, "0.02~0.12" can be, for example, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, etc.; Among them, "0.01~0.08" can be, for example, 0.01, 0.02, 0.04, 0.06, 0.08, etc.; Among them, "0.01~0.2" can be, for example, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, etc.

[0086] As an optional implementation, the buffer includes any one or a combination of at least two of MES (2-morpholinoethanesulfonic acid) buffer, HEPES (4-hydroxyethylpiperazine ethanesulfonic acid) buffer, and PBS (phosphate buffer).

[0087] As an optional implementation, the pH of the buffer solution is 5.0 to 6.0, for example, it can be 5.0, 5.2, 5.4, 5.5, 5.6, 5.8, 6.0, etc.

[0088] As an optional implementation, the concentration of the buffer solution is 0.02~0.1 mol / L, for example, it can be 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, etc.

[0089] As an optional implementation, the mass ratio of the low-substituted sodium carboxymethyl cellulose to the buffer solution is 1:(15~25), for example, it can be 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, etc.

[0090] As an optional implementation, the temperature of the amidation reaction is 20~40℃, for example, it can be 20℃, 22℃, 24℃, 26℃, 28℃, 30℃, 32℃, 34℃, 36℃, 38℃, 40℃, etc., and the time of the amidation reaction is 1~3 h, for example, it can be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, etc.

[0091] As an optional implementation, the concentration of the high-salt aqueous solution is 0.5~2 mol / L, for example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, etc.

[0092] As an optional implementation, the solute salt in the high-salt aqueous solution includes sodium chloride and / or sodium sulfate.

[0093] As an optional implementation, the washing temperature of the high-salt aqueous solution is 50~60℃, for example, it can be 50℃, 51℃, 52℃, 53℃, 54℃, 55℃, 56℃, 57℃, 58℃, 59℃, 60℃, etc., and the washing time of the high-salt aqueous solution is 30~90 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, etc.

[0094] As an optional implementation, the second etherification reaction includes the following steps: A mixed solution is obtained by mixing alkali, sodium chloroacetate, pH buffer, ethanol, and water. The grafted guanidine salt low-substituted sodium carboxymethyl cellulose fiber is placed in the mixed solution for treatment, followed by neutralization, washing, and drying to obtain the grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber.

[0095] It should be noted that during the second etherification treatment, since the cellulose fibers already have a certain degree of substitution and the second etherification uses an ethanol-water system, the amount of sodium hydroxide and sodium chloroacetate used is greatly reduced. In order to prevent excessive hydrolysis of the grafted guanidine compounds, the sodium hydroxide ethanol aqueous solution is heated to the reaction temperature before the dissolved sodium chloroacetate solution is added, and then the low-substituted carboxymethyl cellulose sodium fiber is added for the second etherification reaction. Since the pH is about 13 at the beginning of the reaction, the guanidine compounds will partially hydrolyze. However, as the reaction proceeds rapidly, the pH drops rapidly to about 9-10, at which point the degradation of the guanidine compounds is slow.

[0096] As an optional implementation, during the second etherification reaction, the mixed solution comprises, by mass percentage: 0.5-1.5% alkali (e.g., 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%), 1-3% sodium chloroacetate (e.g., 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%), 0.1-0.5% pH buffer, with the balance being an aqueous ethanol solution.

[0097] As an optional implementation, the base used in the second etherification reaction is sodium hydroxide.

[0098] As an optional implementation, during the second etherification reaction, the pH buffer includes any one or a combination of at least two of sodium lactate, sodium citrate, sodium acetate, sodium hydrogen phosphate, and sodium dihydrogen phosphate.

[0099] As an optional implementation, during the second etherification reaction, the volume ratio of ethanol to water in the aqueous ethanol solution is (75~85):(25~15), for example, it can be 75:25, 76:24, 77:23, 78:22, 79:21, 80:20, 81:19, 82:18, 83:17, 84:16, 85:15, etc.

[0100] As an optional implementation, during the second etherification reaction, the mass ratio of the grafted guanidine salt low-substituted carboxymethyl cellulose sodium fiber to the mixed solution is 1:(15~25), for example, it can be 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, etc.

[0101] As an optional implementation, during the second etherification reaction, the treatment temperature is 60~80℃, for example, it can be 60℃, 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃, 78℃, 80℃, etc., and the treatment time is 0.5~1.5 h, for example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, etc.

[0102] As an optional implementation, during the second etherification reaction, the neutralization is performed using an acidic pH adjuster.

[0103] As an optional implementation, during the second etherification reaction, the acidic pH adjuster includes any one or a combination of at least two of lactic acid, citric acid, acetic acid, sodium lactate, and sodium dihydrogen phosphate.

[0104] In a preferred embodiment, during the second etherification reaction, the acidic pH adjuster is lactic acid and sodium lactate.

[0105] As an optional implementation, during the second etherification reaction, the pH of the neutralized fiber is 5 to 7, for example, it can be 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, etc.

[0106] As an optional implementation, the washing process during the second etherification reaction is performed using an aqueous ethanol solution.

[0107] As an optional implementation, during the second etherification reaction, the volume ratio of ethanol to water in the aqueous ethanol solution is (70~80):(30~20), for example, it can be 70:30, 71:29, 72:28, 73:27, 74:26, 75:25, 76:24, 77:23, 78:22, 79:21, 80:20, etc.

[0108] In a second aspect, the present invention provides a non-overflow antibacterial hydrophilic fiber, wherein the non-overflow antibacterial hydrophilic fiber is prepared by the preparation method of the non-overflow antibacterial hydrophilic fiber as described in the first aspect.

[0109] Thirdly, the present invention provides a non-overflow antibacterial hydrophilic fiber dressing, the non-overflow antibacterial hydrophilic fiber dressing comprising grafted guanidine salt-based highly substituted sodium carboxymethyl cellulose fiber prepared by the preparation method of the non-overflow antibacterial hydrophilic fiber described in the first aspect, or the non-overflow antibacterial hydrophilic fiber described in the second aspect.

[0110] Fourthly, the present invention provides a method for preparing a non-overflowing antibacterial hydrophilic fiber dressing as described in the third aspect, the method comprising: The grafted guanidine salt highly substituted carboxymethyl cellulose sodium fiber or the non-overflow antibacterial hydrophilic fiber is needle-punched to form a nonwoven fabric, thereby obtaining the non-overflow antibacterial hydrophilic fiber dressing.

[0111] As an optional implementation method, the weight is controlled at 100~400g / m³. 2 The pre-puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the main puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the main puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the net walking speed is 0.5~2 m / min.

[0112] Fifthly, the present invention provides the use of a non-overflowing antimicrobial hydrophilic fiber dressing according to the second aspect or the third aspect in the preparation of a wound dressing having absorbent and / or gel-forming properties.

[0113] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0114] It should be noted that the test methods for the degree of substitution, grafting rate, and antibacterial rate of each sample in the following examples and comparative examples are as follows: Taking sodium carboxymethyl cellulose and PHMB (polyhexamethylene biguanide hydrochloride) as examples, the theoretical maximum guanidine grafting rate of sodium carboxymethyl cellulose with different degrees of substitution was calculated: assuming the degree of substitution of sodium carboxymethyl cellulose fiber is 0.1, the number of moles of carboxyl groups on 10g of sodium carboxymethyl cellulose was calculated. The degree of substitution was tested using the ashing method (GB1886.232—2016).

[0115] Cellulose glucose unit (AGU): Molecular formula: C6H 10 O5, molecular weight: 162 g / mol; Carboxymethyl substituent (-CH2COOH): Molecular formula: C2H3O2 (each H is replaced after substitution), molecular weight: 59 g / mol; A degree of substitution DS = 0.1 indicates that each glucose unit has an average of 0.1 carboxymethyl substituents. After substitution, the molecular weight of sodium carboxymethyl cellulose is 162 + (59) 1)×0.1=162+5.8=167.8 g / mol; Number of carboxyl groups in moles = (10 / 167.8 × DS) mol = 0.0596 × 0.1 = 0.00596 mol; The molecular weight of the repeating unit structure of PHMB (excluding free hydrochloride) is 278 g / mol; A carboxyl group is amidated with a repeating structural unit of PHMB. Therefore, the maximum grafting rate of PHMB on sodium carboxymethyl cellulose with a degree of substitution of 0.1 is 0.00596×278 / 10×100%=16.57%, while a grafting rate of less than 10% of PHMB already has an antibacterial rate of more than 99.99% for 7 days.

[0116] Example 1 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. The raw material Tencel was mixed with an aqueous solution of sodium hydroxide, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, and water were 1 kg, 0.8 kg, and 15 kg, respectively. 0.2 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 1 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. The mixture was then washed with water and dried to obtain sodium carboxymethyl cellulose with a low degree of substitution. The degree of substitution of the sodium carboxymethyl cellulose was determined to be 0.2. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Perform an amidation reaction at 25°C for 120 min. The MES buffer solution concentration is 0.05 mol / L, and the pH is 5.5–6.0. ​​The mass ratio of the condensing agent, activator, guanidine compound, and sodium carboxymethyl cellulose is 1:0.08:0.04:0.02. S3. Wash the fiber with 1 mol / L sodium chloride solution (20 times the fiber mass volume) at 55±5℃ for 60 min. Centrifuge the fiber and wash it three times with 20 times the fiber mass volume of pure water. Dry the fiber at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The grafting amount of PHMB in the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 1.4%, the PHMB utilization rate was 70%, and the mass of low-substituted carboxymethyl cellulose sodium fiber was 1.05 kg. S4. Dissolve 0.2 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70°C and add sodium chloroacetate aqueous solution (0.4 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Then, immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.2 kg of lactic acid and neutralize at 45±5°C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80°C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the fiber is tested to be 0.4. S5. The grafted guanidine salt-based highly substituted carboxymethyl cellulose sodium fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein, the process parameters for the needle-punching treatment include: weight control at 200 g / m². 2 The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0117] The infrared spectra of the raw material Tencel used in this embodiment and the resulting antibacterial wound dressing are shown below. Figure 2 .from Figure 2 It can be seen that, compared to the raw material Tencel, the antibacterial wound dressing prepared in this embodiment has a lower viscosity at 1558 cm⁻¹. -1 Nearby and 1667 cm -1 The presence of amide bond characteristic peaks nearby indicates that PHMB was successfully grafted onto carboxymethyl cellulose to obtain the target product.

[0118] Example 2 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. The raw material Tencel was mixed with an aqueous solution of sodium hydroxide, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, and water were 1 kg, 0.8 kg, and 15 kg, respectively. 0.3 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 1 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. The mixture was then washed with water and dried to obtain sodium carboxymethyl cellulose with a low degree of substitution. The degree of substitution of the sodium carboxymethyl cellulose was determined to be 0.2. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Perform an amidation reaction at 25°C for 120 min. The MES buffer solution concentration is 0.05 mol / L, and the pH is 5.5–6.0. ​​The mass ratio of condensing agent, activator, guanidine compound, and sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.16:0.08:0.1. S3. Wash the fiber with 20 times its weight volume of 1 mol / L sodium chloride solution at 55±5℃ for 60 min. After centrifugation, wash the fiber three times with 20 times its weight volume of pure water and dry it at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The grafting amount of PHMB in the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 5.5%, the PHMB utilization rate was 55%, and the weight of the low-substituted carboxymethyl cellulose sodium fiber was 1.06 kg. S4. Dissolve 0.2 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70 °C and add sodium chloroacetate aqueous solution (0.4 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Then, immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.2 kg of lactic acid and neutralize at 45±5 °C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80 °C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the fiber is tested to be 0.4. S5. The grafted guanidine salt-derived highly substituted sodium carboxymethyl cellulose fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein the basis weight is controlled at 200 g / m². 2 The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0119] Example 3 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. Tencel raw material was mixed with an aqueous solution of sodium hydroxide, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The masses of the raw material Tencel, sodium hydroxide, and water were 1 kg, 0.8 kg, and 15 kg, respectively. 0.3 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 1 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. The mixture was then washed with water and dried to obtain sodium carboxymethyl cellulose with a low degree of substitution. The degree of substitution of this sodium carboxymethyl cellulose was determined to be 0.2. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Control the reaction temperature at 25℃ for amidation reaction and the reaction time at 120 min. The concentration of the MES buffer solution is 0.05 mol / L, and the pH is 5.5~6.0. The mass ratio of condensing agent, activator, guanidine compound to sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.32:0.16:0.2. S3. Wash the fiber with 20 times its weight volume of 1 mol / L sodium chloride solution at 55±5℃ for 60 min. Centrifuge the fiber and wash it three times with 20 times its weight volume of pure water. Dry the fiber at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The PHMB grafting amount of the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 9.2%, the PHMB utilization rate was 46%, and the weight of the low-substituted carboxymethyl cellulose sodium fiber was 1.06 kg. S4. Dissolve 0.2 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70°C and add an aqueous solution of sodium chloroacetate (0.4 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.2 kg of lactic acid and neutralize at 45±5°C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80°C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber; the degree of substitution of the fiber is tested to be 0.4. S5. The grafted guanidine salt-based highly substituted carboxymethyl cellulose sodium fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein, the process parameters for the needle-punching treatment include: weight control at 200 g / m². 2 The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0120] Example 4 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. Tencel (a raw material) was mixed with an aqueous solution of sodium hydroxide, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The masses of the raw material Tencel, sodium hydroxide, and water were 1 kg, 0.6 kg, and 15 kg, respectively. 0.25 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 0.6 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. The mixture was then washed with water and dried to obtain sodium carboxymethyl cellulose with a low degree of substitution. The degree of substitution of this sodium carboxymethyl cellulose was determined to be 0.1. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Control the reaction temperature at 25℃ for amidation reaction and the reaction time at 120 min. The concentration of the MES buffer solution is 0.05 mol / L, and the pH is 5.5~6.0. The mass ratio of condensing agent, activator, guanidine compound to sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.08:0.04:0.02. S3. Wash the fiber with 20 times its weight volume of 1 mol / L sodium chloride solution at 55±5℃ for 60 min. Centrifuge the fiber and wash it three times with 20 times its weight volume of pure water. Dry the fiber at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The PHMB grafting amount of the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 1.2%, the PHMB utilization rate was 60%, and the weight of the low-substituted carboxymethyl cellulose sodium fiber was 1.05 kg. S4. Dissolve 0.2 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70 °C and add sodium chloroacetate aqueous solution (0.4 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Then, immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.2 kg of lactic acid and neutralize at 45±5 °C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80 °C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the fiber is tested to be 0.35. S5. The grafted guanidine salt-based highly substituted carboxymethyl cellulose sodium fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein, the process parameters for the needle-punching treatment include: weight control at 200 g / m². 2The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0121] Example 5 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. The raw material Tencel was mixed with an aqueous solution of sodium hydroxide, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, and water were 1 kg, 1.2 kg, and 15 kg, respectively. 0.4 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 1.2 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. After washing with water and drying, sodium carboxymethyl cellulose with a low degree of substitution was obtained. The degree of substitution of the sodium carboxymethyl cellulose was determined to be 0.25. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Control the reaction temperature at 25℃ for amidation reaction and the reaction time at 120 min. The concentration of the MES buffer solution is 0.05 mol / L, and the pH is 5.5~6.0. The mass ratio of condensing agent, activator, guanidine compound to sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.08:0.04:0.02. S3. Wash the fiber with 20 times its weight volume of 1 mol / L sodium chloride solution at 55±5℃ for 60 min. After centrifugation, wash the fiber three times with 20 times its weight volume of pure water and dry it at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The grafting amount of PHMB in the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 1.46%, the PHMB utilization rate was 73%, and the weight of the low-substituted carboxymethyl cellulose sodium fiber was 1.05 kg. S4. Dissolve 0.2 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70°C and add sodium chloroacetate aqueous solution (0.4 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Then, immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.2 kg of lactic acid and neutralize at 45±5°C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80°C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the fiber is tested to be 0.43. S5. The grafted guanidine salt-derived highly substituted sodium carboxymethyl cellulose fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein the basis weight is controlled at 200 g / m². 2 The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0122] Example 6 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. Tencel raw material was mixed with an aqueous sodium hydroxide solution, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, and water were 1 kg, 0.8 kg, and 15 kg, respectively. 0.3 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 1 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. The mixture was then washed with water and dried to obtain sodium carboxymethyl cellulose with a low degree of substitution. The degree of substitution of this sodium carboxymethyl cellulose was determined to be 0.2. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Control the reaction temperature at 25℃ for amidation reaction and the reaction time at 120 min. The concentration of the MES buffer solution is 0.05 mol / L, and the pH is 5.5~6.0. The mass ratio of condensing agent, activator, guanidine compound to sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.08:0.04:0.02. S3. Wash the fiber with 1 mol / L sodium chloride solution (20 times the fiber mass volume) at 55±5℃ for 60 min. Centrifuge the fiber and wash it three times with 20 times the fiber mass volume of pure water. Dry the fiber at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The grafting amount of PHMB in the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 1.4%, the PHMB utilization rate was 70%, and the mass of low-substituted carboxymethyl cellulose sodium fiber was 1.05 kg. S4. Dissolve 0.25 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70°C and add an aqueous solution of sodium chloroacetate (0.5 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.25 kg of lactic acid and neutralize at 45±5°C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80°C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber; the degree of substitution of the fiber is tested to be 0.5. S5. The grafted guanidine salt-based highly substituted carboxymethyl cellulose sodium fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein, the process parameters for the needle-punching treatment include: weight control at 200 g / m². 2 The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0123] Example 7 This embodiment provides a non-overflowing antibacterial hydrophilic fiber dressing, the preparation process of which is as follows: S1. Tencel raw material was mixed with an aqueous sodium hydroxide solution, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, and water were 1 kg, 0.8 kg, and 15 kg, respectively. 0.3 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 1 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. The mixture was then washed with water and dried to obtain sodium carboxymethyl cellulose with a low degree of substitution. The degree of substitution of this sodium carboxymethyl cellulose was determined to be 0.2. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose with a low degree of substitution. Control the reaction temperature at 25℃ for amidation reaction and the reaction time at 120 min. The concentration of the MES buffer solution is 0.05 mol / L, and the pH is 5.5~6.0. The mass ratio of condensing agent, activator, guanidine compound to sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.08:0.04:0.02. S3. Wash the fiber with 20 times its weight volume of 1 mol / L sodium chloride solution at 55±5℃ for 60 min. Centrifuge the fiber and wash it three times with 20 times its weight volume of pure water. Dry the fiber at 80℃ to obtain antibacterial low-substituted carboxymethyl cellulose sodium fiber. The PHMB grafting amount of the antibacterial low-substituted carboxymethyl cellulose sodium fiber was determined to be 1.4%, the PHMB utilization rate was 70%, and the weight of the low-substituted carboxymethyl cellulose sodium fiber was 1.05 kg. S4. Dissolve 0.3 kg of sodium hydroxide in 1.2 kg of pure water and mix with 16.8 L of 95% ethanol. Heat to 70°C and add an aqueous solution of sodium chloroacetate (0.6 kg of sodium chloroacetate dissolved in 2 kg of pure water). At this point, the ethanol volume fraction of the mixture is 80%. Immediately add 1 kg of low-substituted sodium carboxymethyl cellulose fiber and maintain the temperature for 1 h. Then, add 0.25 kg of lactic acid and neutralize at 45±5°C for 30 min. After centrifugation, wash twice with 20 L of 75% ethanol aqueous solution and dry at 80°C to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber; the degree of substitution of the fiber is tested to be 0.6. S5. The grafted guanidine salt-based highly substituted carboxymethyl cellulose sodium fibers are needle-punched into a nonwoven fabric to obtain the non-overflowing antibacterial hydrophilic fiber dressing; wherein, the process parameters for the needle-punching treatment include: weight control at 200 g / m². 2 The pre-puncture depth is 5 mm; the puncture frequency is 550 Hz; the main puncture depth is 6 mm; the puncture frequency is 650 Hz; the main puncture depth is 5.5 mm; the puncture frequency is 550 Hz; and the net walking speed is 1.2 m / min.

[0124] Example 8 This embodiment provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Embodiment 1 only in that polyhexamethylene biguanide hydrochloride is replaced with an equal mass of polyhexamethylene biguanide hydrochloride, while the other steps are the same as in Embodiment 1.

[0125] Example 9 This embodiment provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Embodiment 1 only in that the high-salt aqueous solution is replaced with an aqueous solution of potassium chloride of the same concentration, while the other steps are the same as in Embodiment 1.

[0126] Example 10 This embodiment provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Embodiment 1 only in that the concentration of the high-salt aqueous solution is 0.5 mol / L, while the other steps are the same as in Embodiment 1.

[0127] Example 11 This embodiment provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Embodiment 1 only in that the concentration of the high-salt aqueous solution is 2 mol / L, while the other steps are the same as in Embodiment 1.

[0128] Comparative Example 1 This comparative example provides a non-overflowing antibacterial hydrophilic fiber dressing, which differs from Example 1 only in that the first etherification reaction in step S1 is adjusted so that after directly preparing sodium carboxymethyl cellulose (degree of substitution of 0.4) with a high degree of substitution in step S1, the treatment in S2~S3 is performed, but the second etherification reaction in S4 is no longer performed. Specifically: S1: Tencel raw material was mixed with sodium hydroxide aqueous solution, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, ethanol, and water were 1 kg, 0.5 kg, 15 kg, and 5 kg, respectively. 0.1 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 0.6 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. After washing with water and drying, sodium carboxymethyl cellulose with a high degree of substitution was obtained. The degree of substitution of the sodium carboxymethyl cellulose was determined to be 0.4. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose fiber. Perform an amidation reaction at 30°C for 120 min. The MES buffer solution concentration is 0.05 mol / L, and the pH is 5.5–6.0. ​​The mass ratio of condensing agent, activator, guanidine compound, and sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.08:0.04:0.02. The reaction solvent is an ethanol / water mixture with an ethanol concentration of 75%. S3. Wash with 75% alcohol at 20 times the fiber mass volume for 60 min, repeat 3 times, and then dry at 80℃ to obtain antibacterial sodium carboxymethyl cellulose fiber.

[0129] Comparative Example 2 This comparative example provides a non-overflowing antibacterial hydrophilic fiber dressing. The only difference from Example 1 is that the first etherification reaction in step S1 is adjusted so that after directly preparing sodium carboxymethyl cellulose with a medium degree of substitution (0.3) in step S1, the treatment in S2-S4 is performed. The other steps are the same as in Example 1. Specifically: S1: Tencel raw material was mixed with sodium hydroxide aqueous solution, and the reaction temperature was controlled within the range of 35±5℃ for 30 min. The mass of the raw material Tencel, sodium hydroxide, ethanol, and water were 1 kg, 0.4 kg, 15 kg, and 5 kg, respectively. 0.8 kg of sodium chloroacetate was added, and the reaction temperature was controlled within the range of 70±5℃ for 90 min. Then, 0.5 kg of lactic acid was added for neutralization, and the reaction temperature was controlled within the range of 45±5℃ for 60 min. After washing with water and drying, sodium carboxymethyl cellulose with a moderate degree of substitution was obtained. The degree of substitution of the sodium carboxymethyl cellulose was determined to be 0.3. S2. Prepare a MES buffer solution containing condensing agent EDC, activator NHS, and guanidine compound polyhexamethylene biguanide hydrochloride (PHMB), then add sodium carboxymethyl cellulose fiber. Perform an amidation reaction at 30°C for 120 min. The MES buffer solution concentration is 0.05 mol / L, and the pH is 5.5–6.0. ​​The mass ratio of condensing agent, activator, guanidine compound, and sodium carboxymethyl cellulose is: sodium carboxymethyl cellulose: condensing agent: activator: guanidine compound = 1:0.08:0.04:0.02. The reaction solvent is an ethanol / water mixture with an ethanol concentration of 75%. S3. Wash with 75% alcohol at 20 times the fiber mass volume for 60 min, repeat 3 times, and then dry at 80℃ to obtain antibacterial sodium carboxymethyl cellulose fiber.

[0130] Comparative Example 3 This comparative example provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Example 1 only in that, in step S3, sodium chloride solution is no longer used for washing; instead, it is washed three times with a 75% ethanol aqueous solution. The other steps are the same as in Example 1.

[0131] Comparative Example 4 This comparative example provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Example 1 only in that, in step S3, sodium chloride solution is no longer used for washing; instead, it is washed 6 times with a 75% ethanol aqueous solution. The other steps are the same as in Example 1.

[0132] Comparative Example 5 This comparative example provides a non-overflow antibacterial hydrophilic fiber dressing, which differs from Example 1 only in that, in step S3, sodium chloride solution is no longer used for washing; instead, it is washed 9 times with a 75% ethanol aqueous solution. The other steps are the same as in Example 1.

[0133] Test case Test method: (1) The grafting amount of guanidine compounds was determined according to Appendix A of the standard GB 26367-2020 Hygienic Standard for Guanidine Disinfectants.

[0134] (2) A 3*3cm nonwoven fabric sample was extracted with 20ml of solution A (a solution composed of sodium chloride and calcium chloride, containing 142mmol sodium ions and 2.5mmol calcium ions, the ion content of which is equivalent to human serum or wound exudate. 8.298g sodium chloride and 0.368g calcium chloride dihydrate were dissolved in deionized water in a volumetric flask and diluted to 1L). The content of guanidine compounds in the extract was determined by visible spectrophotometry.

[0135] (3) Liquid absorption: Weigh 0.5g of the sample that has been dried at 100℃ for 2h in a petri dish, add 20g of solution A, let it stand at 25℃ for 30min, then take it out with tweezers and hang it for 30s. Weigh the weight W after absorbing the test solution A, and calculate the liquid absorption. The calculation formula is: (W-0.5) / 0.5*100%.

[0136] (4) Liquid-locking ability: Cut a 50mm*50mm sample and weigh W1; place the sample in a petri dish and add a certain amount of solution A to make the sample saturated with liquid; place the saturated sample on a flat surface and apply a pressure of 40mmHg (about 1.36kg) to the sample surface (50*50mm) for 5min to absorb the liquid seeping out around the sample, take out the sample and weigh W2; place enough filter paper on the sample, remove the filter paper after 30min and weigh the sample W3; calculate its liquid-locking ability according to the following formula: (W3-W1) / (W2-W1)*100%.

[0137] (5) Test the antibacterial properties of needle-punched nonwoven fabric and the antibacterial properties of extract after 7 days. GBT 20944.3-2008 Evaluation of antibacterial properties of textiles - Part 3: Shaking method. The test species are Staphylococcus aureus (ATCC 6538), Escherichia coli (ATCC 25922), and Candida albicans (ATCC 10231).

[0138] The specific test results are shown in Table 1: Table 1

[0139] As shown in Table 1, the non-overflow antibacterial hydrophilic fiber dressing prepared by this invention achieves a synergistic improvement in water absorption and retention performance, antibacterial efficacy, and biocompatibility. The dressing possesses excellent exudate absorption and retention capabilities, maintaining a moist healing environment for the wound; it exhibits highly effective and stable antibacterial activity against common pathogens, providing long-lasting protection against the risk of wound infection. The guanidine antibacterial components are firmly bound to the fiber matrix via covalent bonds, with no antibacterial substances precipitated during use, and the extract exhibiting no antibacterial activity, completely eliminating the safety risks associated with the release of free antibacterial components. It also demonstrates excellent biocompatibility, making it suitable for various wound care needs.

[0140] As can be seen from the comparison of Examples 1-7, all groups achieved highly efficient and stable antibacterial effects, and the extracts showed no free guanidine precipitation and no antibacterial activity, verifying the strongness of covalent grafting and the thoroughness of high-salt washing, demonstrating excellent biosafety. Furthermore, increasing the dosage of guanidine antibacterial agents, condensing agents, and activators can correspondingly increase the grafting amount of antibacterial components onto the fibers. However, the utilization rate of antibacterial raw materials decreases with increasing dosage; the ratio can be flexibly adjusted according to antibacterial requirements and cost control. Increasing the initial low degree of substitution provides more reaction sites for the amidation reaction, improving reaction efficiency, but it must be controlled within the critical range where the fiber does not gel upon contact with water to ensure the feasibility of the aqueous phase reaction. Increasing the final degree of substitution can significantly enhance the dressing's absorbency and retention capacity; hydrophilic properties can be precisely controlled through secondary etherification.

[0141] As can be seen from the comparison between Example 1 and Comparative Example 1, using alcohol as a solvent to graft guanidine antibacterial agents results in problems such as incomplete grafting and incomplete washing of the guanidine antibacterial agents, leading to the release of guanidine antibacterial agents during use.

[0142] As can be seen from the comparison of Example 1, Comparative Example 1 and Comparative Example 2, using alcohol as a solvent to graft guanidine antibacterial agents results in problems such as incomplete grafting and incomplete washing of the guanidine antibacterial agents. During use, guanidine antibacterial agents will be released. At the same time, the degree of substitution will also affect the degree of grafting of guanidine antibacterial agents onto sodium carboxymethyl cellulose.

[0143] As can be seen from the comparison between Example 1 and Comparative Examples 3-5, repeated washing of grafted guanidine fibers with ethanol-water solution has obvious purification defects and process limitations. Specifically, the ethanol-water solution cannot destroy the strong electrostatic adsorption between the anionic skeleton of carboxymethyl cellulose and the cationic PHMB, thus only washing away a small amount of free guanidine substances on the fiber surface. Even with increased washing cycles, the residual PHMB electrostatically adsorbed in the fiber pores cannot be completely removed, and the extract retains its antibacterial activity, failing to meet the medical requirement of zero spillage of antibacterial components. Furthermore, repeated washing with ethanol-water solution lengthens the process, increases production costs, and the organic solvent waste increases environmental treatment pressure and poses biosafety risks.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a non-overflowing antibacterial hydrophilic fiber, characterized in that, include: The fiber raw material undergoes a first etherification reaction to obtain sodium carboxymethyl cellulose with a low degree of substitution; After the sodium carboxymethyl cellulose with low degree of substitution and guanidine compounds undergo an amidation reaction, it is washed with a high-salt aqueous solution to obtain sodium carboxymethyl cellulose fiber with grafted guanidine salts. The grafted guanidine salt low-substituted sodium carboxymethyl cellulose fiber undergoes a second etherification reaction to obtain grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. The degree of substitution of the low-substituted sodium carboxymethyl cellulose is less than 0.25; the degree of substitution of the grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber is greater than 0.

35.

2. The method for preparing non-overflow antibacterial hydrophilic fibers according to claim 1, characterized in that, The first etherification reaction includes the following steps: The fiber raw material is first treated with an alkaline solution, then treated with a sodium chloroacetate solution, and finally neutralized, washed, and dried to obtain the sodium carboxymethyl cellulose with low degree of substitution. Preferably, the fiber raw material includes any one or a combination of at least two of Tencel fiber, cotton fiber, bamboo fiber, and viscose fiber, with Tencel fiber being the most preferred. Preferably, the alkali solution contains 2-8% alkali by mass; the mass ratio of the fiber raw material to the alkali solution is 1:(10-20); the alkali treatment temperature is 25-40°C; the alkali treatment time is 20-40 min; and the alkali is sodium hydroxide. Preferably, the sodium chloroacetate solution contains 5-20% sodium chloroacetate by mass; the mass ratio of the fiber raw material to sodium chloroacetate is 1:(0.2-0.4); the sodium chloroacetate solution is treated at a temperature of 60-80°C; and the sodium chloroacetate solution is treated for 1-3 hours. Preferably, the neutralization employs an acidic pH adjuster; the acidic pH adjuster includes any one or a combination of at least two of lactic acid, citric acid, acetic acid, and hydrochloric acid, preferably lactic acid; Preferably, the pH of the neutralized fiber is 5-7; Preferably, the washing process uses pure water.

3. The method for preparing non-overflow antibacterial hydrophilic fibers according to claim 1, characterized in that, The amidation reaction includes the following steps: A condensing agent, activator, guanidine compound, buffer solution, and sodium carboxymethyl cellulose with low substitution degree are mixed to carry out an amidation reaction; Preferably, the condensing agent comprises carbodiimide compounds, preferably any one or a combination of at least two of EDC, DCC, and DIC; Preferably, the activator includes NHS and / or HOBt; Preferably, the guanidine compound includes any one or a combination of at least two of polyhexamethylene guanidine and its derivatives, and polyhexamethylene biguanide and its derivatives; Preferably, the mass ratio of the condensing agent, activator, guanidine compound, and sodium carboxymethyl cellulose with low substitution degree is 1:(0.02~0.12):(0.01~0.08):(0.01~0.2); Preferably, the buffer solution comprises any one or a combination of at least two of MES buffer, HEPES buffer, and PBS buffer; the pH of the buffer solution is 5.0-6.0, and the concentration of the buffer solution is 0.02-0.1 mol / L; the mass ratio of the low-substituted sodium carboxymethyl cellulose to the buffer solution is 1:(15-25). Preferably, the amidation reaction is carried out at a temperature of 20-30°C for 1-3 hours.

4. The method for preparing non-overflow antibacterial hydrophilic fibers according to claim 1, characterized in that, The concentration of the high-salt aqueous solution is 0.5~2 mol / L; Preferably, the solute salt in the high-salt aqueous solution includes sodium chloride and / or sodium sulfate; Preferably, the washing temperature of the high-salt aqueous solution is 50~60℃, and the washing time of the high-salt aqueous solution is 30~90min.

5. The method for preparing non-overflow antibacterial hydrophilic fibers according to claim 1, characterized in that, The second etherification reaction includes the following steps: A mixed solution is obtained by mixing alkali, sodium chloroacetate, pH buffer, ethanol, and water. The grafted guanidine salt low-substituted sodium carboxymethyl cellulose fiber is placed in the mixed solution for treatment, and then neutralized, washed and dried to obtain the grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber. Preferably, the mixed solution comprises, by mass percentage: 0.5-1.5% alkali, 1-3% sodium chloroacetate, 0.1-0.5% pH buffer, with the remainder being an aqueous ethanol solution; the alkali is sodium hydroxide; the pH buffer comprises any one or a combination of at least two of sodium lactate, sodium citrate, sodium acetate, sodium hydrogen phosphate, and sodium dihydrogen phosphate; the volume ratio of ethanol to water in the aqueous ethanol solution is (75-85):(25-15). Preferably, the mass ratio of the grafted guanidine salt low-substituted carboxymethyl cellulose sodium fiber to the mixed solution is 1:(15~25); Preferably, the treatment temperature is 60~80℃, and the treatment time is 0.5~1.5 h; Preferably, the neutralization employs an acidic pH adjuster; the acidic pH adjuster includes at least one of lactic acid, citric acid, acetic acid, sodium lactate, and sodium dihydrogen phosphate, preferably lactic acid and sodium lactate; Preferably, the pH of the neutralized fiber is 5-7; Preferably, the washing process uses an aqueous ethanol solution; the volume ratio of ethanol to water in the aqueous ethanol solution is (70~80):(30~20).

6. A non-overflowing antibacterial hydrophilic fiber, characterized in that, The non-overflow antibacterial hydrophilic fiber is prepared by the method for preparing non-overflow antibacterial hydrophilic fiber according to any one of claims 1 to 5.

7. A non-overflowing antibacterial hydrophilic fiber dressing, characterized in that, The non-overflow antibacterial hydrophilic fiber dressing comprises grafted guanidine salt high-substituted sodium carboxymethyl cellulose fiber prepared by the preparation method of non-overflow antibacterial hydrophilic fiber according to any one of claims 1 to 5, or the non-overflow antibacterial hydrophilic fiber according to claim 6.

8. A method for preparing a non-overflowing antibacterial hydrophilic fiber dressing according to claim 7, characterized in that, The preparation method includes: The grafted guanidine salt highly substituted carboxymethyl cellulose sodium fiber or the non-overflow antibacterial hydrophilic fiber is needle-punched to form a nonwoven fabric, thereby obtaining the non-overflow antibacterial hydrophilic fiber dressing.

9. The method for preparing the non-overflow antibacterial hydrophilic fiber dressing according to claim 8, characterized in that, The process parameters for the acupuncture treatment include: weight control of 100~400g / m³. 2 The pre-puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the main puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the main puncture depth is 4~8 mm; the puncture frequency is 400~800 Hz; the net walking speed is 0.5~2 m / min.

10. The use of a non-overflowing antimicrobial hydrophilic fiber dressing according to claim 6 or according to claim 7 in the preparation of a wound dressing having absorbent and / or gel-forming properties.

Citation Information

Patent Citations

  • Simple method for quickly adding silver ion for sterilization for calcium alginate fiber

    CN101187153A

  • Fiber wound dressing with antibacterial effect and preparation method thereof

    CN102462860A

  • Chitosan hydrogel for antibacterial dressing and preparation method thereof

    CN103920180A

  • Wound anti-bacteria dressing and preparation method and application thereof

    CN107137749A

  • Medical antibacterial fiber, preparation method thereof and medical antibacterial dressing

    CN109898323A